Clinical service delivery implications of the COVID-19 pandemic on people with Inflammatory bowel disease: a qualitative study - Karen Kemp; Pearl Avery; Ruby Bryant; Amanda Cross; Kayleigh Danter; Andrew Kneebone; Deborah Morris; Amy Walker; Lisa Whitley; Lesley Dibley (BMC, 2023)
Abstract Background During the COVID-19 pandemic, clinical services were severely disrupted, restricted, or withdrawn across the country. People living with Inflammatory Bowel Disease (IBD) - an auto-immune disorder for which medical treatment often results in immunosuppression, thus requiring regular monitoring-may have struggled to access clinical support. As part of a larger qualitative study, we investigated experiences of access to clinical services during the pandemic, and patient concerns about and preferences for services in the future. Methods This exploratory qualitative study used semi-structured interviews to explore participants' experiences of clinical services across the UK during the pandemic. All data were collected remotely (March - May 2021) using online video-calling platforms or by telephone. Audio files were transcribed professionally and anonymised for analysis. Data were analysed using thematic analysis. Results Of the eight themes found across all data, four related specifically to accessing GP, local (district) hospital, and specialist (tertiary) referral services for IBD: 1) The Risk of Attending Hospital; 2) Missing Routine Monitoring or Treatment; 3) Accessing Care as Needed, and 4) Remote Access and The Future. Conclusions Our findings support other studies reporting changes in use of health services, and concerns about future remote access methods. Maintenance of IBD services in some form is essential throughout crisis periods; newly diagnosed patients need additional support; future dependence on IBD services could be reduced through use of treatment / self-management plans. As the NHS digitalises it's future services, the mode of appointment-remote (telephone, video call), or in-person - needs to be flexible and suit the patient.